Combined Pressure Sensor With Enhanced Dynamic Range Based on Thin Films of Nanotubes and Graphite Nanobelts - Alaferdov, Andrei; Vilkov, Ilya; Kaverin, Boris; Ob´edkov, Anatoly; Moshkalev, Stanislav (Frontiers in Sensors, 2021)
Herein, we demonstrate the prototype of a combined flexible pressure sensor based on ultrathin multiwall carbon nanotubes (MWCNT) and graphite nanobelts (GNBs) films embedded in polydimethylsiloxane (PDMS). A simple and scalable modified Langmuir-Blodgett method was used for deposition of both MWCNT and GNB films. The use of two types of carbon nanostructures (nanotubes and graphite nanobelts) with distinctly different mechanical properties allowed obtaining enhanced dynamic range for the pressure sensing. Short response time, good sensibility and flexibility, low power consumption for enhanced pressure range make possible applications of the sensor for healthcare monitoring and as a component in the human-machine interfaces application.